2012
DOI: 10.1007/s10549-011-1947-7
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent change in biomarkers during neoadjuvant endocrine therapy with fulvestrant: results from NEWEST, a randomized Phase II study

Abstract: NEWEST (Neoadjuvant Endocrine Therapy for Women with Estrogen-Sensitive Tumors) is the first study to compare biological and clinical activity of fulvestrant 500 versus 250 mg in the neoadjuvant breast cancer setting. We hypothesized that fulvestrant 500 mg may be superior to 250 mg in blocking estrogen receptor (ER) signaling and growth. A multicenter, randomized, open-label, Phase II study was performed to compare fulvestrant 500 mg (500 mg/month plus 500 mg on day 14 of month 1) versus fulvestrant 250 mg/mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 16 publications
5
70
0
1
Order By: Relevance
“…Investigators evaluating postmenopausal women with ER+ breast cancer who were receiving neoadjuvant endocrine therapy found that the ER downregulator fulvestrant decreased Ki67, ER and PR expression after 16 weeks of treatment in a dose dependent fashion (34). In a separate study of women who received neoadjuvant chemotherapy for breast cancer, tumor grade changed in 35%, ER, PR and HER2 expression in 43, 55 and 27% of cases, respectively (35).…”
Section: The Effects Of Treatmentmentioning
confidence: 99%
“…Investigators evaluating postmenopausal women with ER+ breast cancer who were receiving neoadjuvant endocrine therapy found that the ER downregulator fulvestrant decreased Ki67, ER and PR expression after 16 weeks of treatment in a dose dependent fashion (34). In a separate study of women who received neoadjuvant chemotherapy for breast cancer, tumor grade changed in 35%, ER, PR and HER2 expression in 43, 55 and 27% of cases, respectively (35).…”
Section: The Effects Of Treatmentmentioning
confidence: 99%
“…In the neoadjuvant setting, the use of fulvestrant is controversial, because of the slow response rate and possible non-response. In a phase Ⅱ randomized study, tumor response rates were 20.6% and 22.9%, according to the dosage of the drug [43] .…”
Section: Down-regulatorsmentioning
confidence: 99%
“…In the metastatic setting, 500 mg fulvestrant, given as 2 Â 250 mg intramuscular injections, has been shown to offer additional benefit over the 250 mg dose with improved median overall survival (7,8). Recent analysis of presurgical data from a number of trials showed a dose-dependent effect on key biomarkers such as ER, progesterone receptor (PR), and Ki67 labeling index (9).…”
Section: Introductionmentioning
confidence: 99%